Brave Norman : a true story - Clements, Andrew, 1949-; Beier, Ellen (New York : Simon & Schuster Books for Young Readers, 2001)
Norman, a blind Labrador retriever, saves a girl from drowning in the ocean.
School Library Journal.
Booklist.
1.5
K-3
Center for the Collaborative Classroom Curriculum.
350L
Keywords: Labrador retriever -- Anecdotes -- Juvenile literature; Dogs; Blind; Lifesaving; Dogs; Blind; Lifesaving; Dogs; Blind; Lifesaving